Instant recall Italian - Gruneberg, Michael M. (New York : McGraw-Hill, 2010)
The Instant Recall series' method works with association and memory by providing easy-to-remember mental pictures to help learners remember words and basic grammar skills in Italian.
Keywords: Italian language -- Sound recordings for English speakers; Italian language -- Spoken Italian; Italian language -- Vocabulary